2007
DOI: 10.1002/adfm.200601117
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Size Bulk and Thin‐Film Stilbazolium‐Salt Single Crystals for Nonlinear Optics and THz Generation

Abstract: We present new stilbazolium salt DSTMS (4‐N,N‐dimethylamino‐4′‐N′‐methyl‐stilbazolium 2,4,6‐trimethylbenzenesulfonate) with both high second‐order nonlinear optical properties and very favorable crystal growth characteristics. We are able to obtain very large area bulk single crystals of more than 3 × 3 × 0.2 cm3 with a high optical quality without using seed crystals by using low‐temperature solution growth. We also demonstrate the growth of single crystalline thin films of DSTMS with an area of up to 6 × 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
220
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(225 citation statements)
references
References 23 publications
(30 reference statements)
2
220
0
Order By: Relevance
“…The regrowth-free approach enables Al-containing epitaxial layers to be used, as there is no exposure of surfaces containing Al, which can oxidize and cause problems during epitaxial regrowth [6]. The results presented in this article suggest that our device could be used as a compact, stable, solid-state practical laser source for generating THz radiation using a photoconductive antenna [7] or nonlinear optical crystal [8].…”
Section: Introductionmentioning
confidence: 87%
“…The regrowth-free approach enables Al-containing epitaxial layers to be used, as there is no exposure of surfaces containing Al, which can oxidize and cause problems during epitaxial regrowth [6]. The results presented in this article suggest that our device could be used as a compact, stable, solid-state practical laser source for generating THz radiation using a photoconductive antenna [7] or nonlinear optical crystal [8].…”
Section: Introductionmentioning
confidence: 87%
“…Yang et al investigated new stilbazolium salts which were grouped into three series with various kinds of counter anions [39]. Comparison of the experimental results ( Figure 3) revealed that introducing especially long counter anions into stilbazolium derivatives does not only restrain the SHG activity but also influences the growth of single crystals.…”
Section: Design Of Anionic Changementioning
confidence: 99%
“…Thus ionic π-conjugated species can be highly polarized when an appropriate substituent is introduced into the cation parts. Therefore, numerous studies on modifying the cation of stilbazolium compounds have been carried out and some interesting achievements have been attained [37][38][39]. As shown in Figure 4, the cation of DAST could be divided into five parts (A-E).…”
Section: Design and Change Of The Stilbazolium Cationmentioning
confidence: 99%
“…We use a nonlinear organic crystal, 4-N, N-dimethylamino -4 -N-methyl-stilbazolium 2,4,6-trimethylbenzenesulfonate (DSTMS), as a medium for nonlinear frequency conversion (Yang et al, 2007). Strong THz pulses are achieved via optical rectification of mJ-level pulses centered around 1.5 mm in wavelength (Hauri et al, 2011).…”
Section: Instrumentationmentioning
confidence: 99%